Herbal Medicine Compared to Placebo for Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Kwon, Chan-Young; Lee, Boram; Lee, Beom-Joon; Kim, Kwan-Il; Jung, Hee-Jae (Frontiers in Pharmacology, 2021)
Chronic obstructive pulmonary disease (COPD) is a respiratory disease characterized by irreversible airflow limitation. Many COPD patients use complementary and alternative modalities, including herbal medicines (HMs). This systematic review investigated the effectiveness and safety of HM in managing COPD symptoms compared to placebo. Nine electronic databases were searched to identify relevant randomized controlled trials (RCTs) up to February 12, 2021. The Cochrane risk of bias tool was used to assess the methodological qualities of the included studies. Primary outcomes were lung function parameters and exercise capacity. A meta-analysis was conducted to determine the effect size for homogeneous outcomes. Fourteen studies were included. There was low to very low quality evidence that HM significantly improved forced expiratory volume in 1 s (FEV1) (L), FEV1 (%) and 6-minute walk distance, as well as moderate quality evidence that HM significantly improved forced vital capacity (FVC) (L) compared to placebo. However, according to low quality evidence, there was no significant difference in FEV1/FVC (%) or vital capacity (L) between the groups. Low to moderate evidence suggests that HM has the potential to help improve some respiratory functions, COPD symptoms, and some aspects of quality of life in COPD patients compared to placebo. However, these findings are challenged by the poor methodological quality of the included studies, the heterogeneity of HMs used, and potential publication bias. Therefore, the findings could be significantly influenced by further larger, more rigorous RCTs on this topic. Moreover, it may also be recommended to develop standardized HMs focused on some individual herbs that are frequently used or expected to play an important role in patients with COPD, and to elucidate the underlying mechanisms.